2020
DOI: 10.1016/j.ejca.2020.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Dutch Oncology COVID-19 consortium: Outcome of COVID-19 in patients with cancer in a nationwide cohort study

Abstract: Aim of the study Patients with cancer might have an increased risk for severe outcome of coronavirus disease 2019 (COVID-19). To identify risk factors associated with a worse outcome of COVID-19, a nationwide registry was developed for patients with cancer and COVID-19. Methods This observational cohort study has been designed as a quality of care registry and is executed by the Dutch Oncology COVID-19 Consortium (DOCC), a nationwide collaboration of oncology physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
106
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(118 citation statements)
references
References 22 publications
9
106
2
1
Order By: Relevance
“…Existing evidence in the general population indicates older individuals and those with comorbid chronic conditions are at higher risk for SARS‐CoV‐2 infection, severe disease, and death 2–5 . Cancer patients may also be at increased risk of adverse outcomes if infected, 6–10 though morbidity and mortality appear to vary across tumor histology and treatment status 11–16 . While recent small studies suggest that pediatric patients with cancer may not be more vulnerable than other children to infection or morbidity from SARS‐CoV‐2, 17,18 other studies suggest that children with hematologic malignancies may have a more severe course of COVID‐19 illness 19 …”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence in the general population indicates older individuals and those with comorbid chronic conditions are at higher risk for SARS‐CoV‐2 infection, severe disease, and death 2–5 . Cancer patients may also be at increased risk of adverse outcomes if infected, 6–10 though morbidity and mortality appear to vary across tumor histology and treatment status 11–16 . While recent small studies suggest that pediatric patients with cancer may not be more vulnerable than other children to infection or morbidity from SARS‐CoV‐2, 17,18 other studies suggest that children with hematologic malignancies may have a more severe course of COVID‐19 illness 19 …”
Section: Introductionmentioning
confidence: 99%
“…In our study, we observed that patients with advanced cancer at COVID-19 diagnosis have a greater risk of continuing to present positive RT-PCR with prolonged COVID-19 symptoms, similar to that observed in hematological patients undergoing transplant or CAR-T cell therapy 7 . In addition, we observed that these patients with advanced disease have the worst prognosis 1 , 2 , like lung cancer patients and hematologic cancer patients 2 , 8 . The advanced state of immunosuppression induced by their cancer and by the specifical oncological treatments received, it could may justify our findings.…”
mentioning
confidence: 78%
“…SARS-CoV-2 is a highly contagious virus and can cause potentially fatal complications in cancer patients 1 , 2 , 3 , 4 . Until now, the most accurate and common methods to detect active viral infection are: (1) a positive RT-PCR, (2) a serological test (IgM+ and IgG-), (3) or a positive antigen test 5 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the first retrospective cohort in China, describing a higher risk of severe events for cancer versus non-cancer patients, data from several multicentric registries including hundreds of cancer patients reported a mortality rate in the range of 10-33%. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 It is important to note, however, the huge heterogeneity of the clinical course of SARS-CoV-2 infection across different countries. Mortality, the most important measure of COVID-19 disease burden, largely differs across countries.…”
Section: Introductionmentioning
confidence: 99%